PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM PEMAHAMAN KONSEP MATEMATIS XI MIPA SMA PERTIWI 1 PADANG - Diyana Rahmatika Utami (Departemen Matematika, 2022)
One of the purposes of learning mathematics was understood the concepts of mathematical expected of students. However, in practice, the SMA Pertiwi 1 Padang is still suboptimal or still low. Existing learning models failed to improve student concepts. Poor concept understanding affects other math skills. The study purpose was found and explained the increased conceptual understanding by students learning in a flipped classroom learning model, and to find out how conceptual understanding is improved in students learning in a flipped classroom learning model. to explain. Better than grasping the students learning concepts in the classroom using direct learning models. Class XI MIPA SMA Pertiwi 1 Padang for 2022/2023. This type of study is a quasi-experimental, descriptive study design by the Non-Equivalent-Only Posttest Design Group. The population is Class XI MIPA SMA Pertiwi 1 Padang and the study samples are Class XI MIPA 1 and XI MIPA 3. Research tools are quizzes and concept comprehension tests. Data on the development of this ability were described by quiz scores and test scores were analyzed using t-tests. The results of the quiz showed that applying the REACT strategy increased the development of conceptual understanding, and the results of the test analysis yielded a t-test P - value = 0.00. , H0 is rejected. This means that in the 2022/2023 XI MIPA SMA Pertiwi 1 Padang class, conceptual understanding by students learning in the flipped classroom learning model is better than by students learning in the direct learning model. Keywords: Understanding Mathematical Concepts, Flipped Classroom learning model, Direct Learning